Partitioning of Microbially Respired CO2 Between Indigenous and Exogenous Carbon Sources During Biochar Degradation Using Radiocarbon and Stable Carbon Isotopes. Issue 2 (5th November 2018) - Munksgaard, Niels C; McBeath, Anna V; Ascough, Philippa L; Levchenko, Vladimir A; Williams, Alan; Bird, Michael I
ABSTRACT: Pyrolized carbon in biochar can sequester atmospheric CO2 into soil to reduce impacts of anthropogenic CO2 emissions. When estimating the stability of biochar, degradation of biochar carbon, mobility of degradation products, and ingress of carbon from other sources must all be considered. In a previous study we tracked degradation in biochars produced from radiocarbon-free wood and subjected to different physico-chemical treatments over three years in a rainforest soil. Following completion of the field trial, we report here a series of in-vitro incubations of the degraded biochars to determine CO2 efflux rates, 14 C concentration and δ 13 C values in CO2 to quantify the contributions of biochar carbon and other sources of carbon to the CO2 efflux. The 14 C concentration in CO2 showed that microbial degradation led to respiration of CO2 sourced from indigenous biochar carbon (≈0.5–1.4 μmoles CO2 /g biochar C/day) along with a component of carbon closely associated with the biochars but derived from the local environment. Correlations between 14 C concentration, δ 13 C values and Ca abundance indicated that Ca 2+ availability was an important determinant of the loss of biochar carbon.